Complicity, crime and conjoined twins. (March 2017) - Davis, Colleen
This article looks at the difficulties facing a court required to sentence a conjoined twin convicted of a criminal offence. If the other conjoined twin could be convicted as a party to the offence, many of the difficulties with punishment could be overcome. In the eyes of the criminal law, a person who aids in or encourages the commission of a crime is as blameworthy as the person who commits the offence. This article argues that the fact that one conjoined twin is inevitably present at a crime committed by the other does not automatically mean that the non-perpetrator is an accessory. Mere presence is not enough – generally, an accessory must intentionally assist or encourage the offender, and must promote or assist in the crime. Further, in the absence of a conviction of the non-perpetrator of the offence as an accessory, it would seem there is no way to punish the guilty conjoined twin without also unjustly punishing the innocent sibling.